The prevalence and contribution of histological patterns to late period renal allograft dysfunction and loss - Saffer, Sara (My University, 2018)
Late period renal allograft dysfunction and loss remains a substantial limitation to transplant longevity. The contribution of various aetiological factors resulting in late period allograft dysfunction and loss at CMJAH and their associated biochemical markers were evaluated. Methods The histological findings in a cohort of patients (n=242) undergoing late post-transplant period (>3 months after engraftment) renal allograft biopsy-for-cause over a 10 year period from 1/1/2004 – 31/12/2013 were retrospectively evaluated. Serum creatinine, urine white cell count, and urine protein: creatinine ratio (UPCR) at the time of biopsy together with percentage change in serum creatinine were analyzed in respect of the histological diagnosis. Results Immunological factors were found to be the dominant cause of graft injury accounting for the majority (50.8%) comprising cell-mediated rejection (CMR) (62%), antibody-mediated rejection (ABMR) and mixed rejection (MR) at 21.7% and 16.3% respectively. Diagnosis of ABMR was observed to increase after the introduction in 2009 of routine C4d staining, suggesting the possibility of under-diagnosis of ABMR during the 2004-2009 periods. Non-immunological causes of graft injury accounted for 49.2% of cases. Calcineurin inhibitor nephrotoxicity (16.9%) was the leading non-immunological aetiological factor identified, followed by reflux nephropathy (6.6%), recurrent / de novo glomerular disease (5.4%), thrombotic microangiopathy (1.6%), BK polyomavirus nephropathy (0.8%), and hypertensive nephropathy (0.8%). Idiopathic interstitial nephritis / tubular atrophy (IFTA) comprised 14.7% of cases; in the remaining 2.1% no obvious cause of graft dysfunction was identified at biopsy. Graft age was lower at diagnosis (p=0.019) and percentage change in serum creatinine was higher in cases of rejection (p=0.00005). Discriminant analysis determined that graft age below 79 months and percentage change in serum creatinine above 23.9% were associated with rejection as a cause of graft dysfunction (OR=1.6772,95% CI 1.006-2.965, p=0.0465 and OR=2.174,95% CI 1.2896-3.6698, p=0.0033) respectively. Comparison of cases of CMR vs. ABMR found a higher UPCR level in ABMR (p=0.039). Discriminant analysis determined that UPCR >0 .20 g/mmol was associated with ABMR (eigenvalue = 0.049, Wilk’s λ = 0.952, χ2 = 5.77, df = 1, p = 0.016). Immunological patterns of injury demonstrated poorer allograft survival after diagnostic biopsy than non-immunological patterns (Cox Mantel test F = 2.155, p = 0.031) Furthermore, the presence of histological features consistent with antibody-mediated injury on retrospective biopsy were found to have significantly deleterious effect on post biopsy outcomes (Cox Mantel F = 2.16, p = 0.031). Conclusion Immunological factors play a significant role in late period graft dysfunction and loss at CMJAH. The contribution of ABMR in limiting long-term graft survival has likely been previously under-estimated due to the lack of a histological marker such as C4d to facilitate diagnosis. Furthermore, consideration of the graft age and percentage change in creatinine from baseline may alert clinicians to the possibility of rejection as cause for late period graft dysfunction. Proteinuria arising as a result of evolving transplant glomerulopathy may indicate the presence of antibody-mediated injury. Since humoral injury is associated with poorer allograft survival; early detection through appreciation of clinical parameters such as proteinuria may facilitate preemptive directed therapy, possibly improving renal allograft survival.
research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Internal Medicine Johannesburg, 2018